2011
DOI: 10.1523/jneurosci.2599-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between “What” and “When” in the Auditory System: Temporal Predictability Enhances Repetition Suppression

Abstract: Neural activity in the auditory system decreases with repeated stimulation, matching stimulus probability in multiple timescales. This phenomenon, known as stimulus-specific adaptation, is interpreted as a neural mechanism of regularity encoding aiding auditory object formation. However, despite the overwhelming literature covering recordings from single-cell to scalp auditory-evoked potential (AEP), stimulation timing has received little interest. Here we investigated whether timing predictability enhances th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(175 citation statements)
references
References 59 publications
11
140
13
Order By: Relevance
“…Recent research has focused on different strategies for disentangling N1 from P2. For example, temporal unpredictability of stimulus occurrence, when compared with fixed inter-stimulus intervals (Pereira et al, 2014), induced differential modulations in N1 and P2 components (Costa-Faidella et al, 2011). Likewise, the presentation of human vocal auditory stimuli induced higher P2 component amplitudes with no effects on the N1 component (Charest et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Recent research has focused on different strategies for disentangling N1 from P2. For example, temporal unpredictability of stimulus occurrence, when compared with fixed inter-stimulus intervals (Pereira et al, 2014), induced differential modulations in N1 and P2 components (Costa-Faidella et al, 2011). Likewise, the presentation of human vocal auditory stimuli induced higher P2 component amplitudes with no effects on the N1 component (Charest et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…In the absence of such a phase reset or if stimuli occur in a non-ideal phase, behavioral responses are suppressed or slowed down. (c) When the timing of a sound is correctly anticipated (right panel), a decrease in evoked auditory responses (N1) is observed [22,23]. This schematic compares the amplitude of an event-related response (N1, averaged across 10 trials) to unexpected (left panel) and expected (right panel) auditory stimuli.…”
Section: Predictive Timing and Delta-theta Oscillationsmentioning
confidence: 99%
“…The predictive alignment of delta-theta oscillations in an ideal excitability phase speeds up stimulus detection (Figure 1b) [20,21]. Furthermore, when stimuli are implicitly expected based on their temporal regularity, early sensory responses are reduced (Figure 1c) [22,23]. The magnitude of neural responses, however, depends on whether temporal predictions are tested in the presence or absence of explicit attention to the nature or location of those events (Box 1 and [24][25][26][27]).…”
Section: Predictive Timing and Delta-theta Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of repetition suppression in both sensory cortices may thus be an index of successful attentional orienting. Additionally, recent findings have shown that the more temporally predictable, the higher the repetition suppression effects notably in the auditory responses (Costa-Faidella et al, 2011;Summerfield et al, 2008Summerfield et al, , 2011. In the context of predictive coding models, it has also been suggested that repetition and expectation were dissociable (Todorovic and de Lange, 2012).…”
Section: Evoked Activity and Attention To Timementioning
confidence: 99%